The Decision of The Ankara Operation After the 1920 Elections in Greece - Kütükçü, Murat (Current Studies in Social Sciences VI, 2023)
Despite all the objections of King Constantine and military advisors, the operation, which started in May 1919 with the support of the Allies, pleased Venizelos supporters. The subsequent elections at November 1920 were a disappointment for Venizelos as well as the continuation of the Anatolian politics of Venizelos, which the new government was initially opposed to, was the beginning of a disaster. When King Constantine and his supporters, came to power in the 1920 General Elections in Greece, contrary to what they thought, Venizelos's choice to continue his Anatolian policy accelerated the failure, first in Sakarya and then in Afyon, against the Turkish Army organized under the leadership of Mustafa Kemal Pasha the fact that they suffered a great defeat brought the end of both themselves and the politics they followed.The famous Greek dream had turned into a Greek nightmare.